A profile of stroke clients treated at the Bishop Lavis Rehabilitation Centre between 1995-1999 - Rhoda, Anthea Joy (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2001.